OVERVIEW OF THE COPING STRATEGY OF FARMERS IN THE FLOOD DISASTER AREA OF WONOASRI VILLAGE, TEMPUREJO DISTRICT, JEMBER REGENCY - Emi Wuryaningsih; Enggal Hadi Kurniyawan; Wahyuni Murti Faiza (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2019)
Disaster flooding in agricultural areas has potential is causing losses, especially crop failures, such as declining farmer economic conditions and declining productivity levels of crops in the agricultural sector this will affect the coping management of farmers in dealing with these problems. This research aims to describe the coping strategies of farmers in Wonoasri Village, Tempurejo District, Jember Regency. The design of this research was a quantitative descriptive. A total of 290 participants have enrolled in this research by using a simple random sampling technique. This research used the characteristics sheet for farmers and the Questionnaire Brief Cope. The results of this research are coping strategies used by farmers are adaptive coping strategies with a median value of 83,00 Â the highest coping is religious coping, behavioral disengagement and substance use.